Analysis of Science Process Skills of Summative Test Items in Physics of Grade X in Surakarta - Ratnasari, D.; Sukarmin, S.; Suparmi, S.; Harjunowibowo, D. (Jurnal Pendidikan IPA Indonesia, 2018)
The objective of this research is to analyze the science process skills (SPS) of the summative test items in physics in Surakarta. This research used a descriptive method with content analysis, namely: summative test items in Academic Year 2015/2016 in Surakarta. Each item was analyzed based on science process skill indicators prepared and elaborated by the researchers. The result and discussion of the research showed that the SPS found in the summative test items in Physics in Surakarta included those of formulating hypotheses (2.88%), designing experiments (2.10%), interpreting data (5.10%), applying concepts (70.20%), communicating (6.64%), and drawing conclusions (13.08%) respectively.